1991
DOI: 10.1021/bi00219a014
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the conformation and stability of Escherichia coli derived-recombinant human interleukin 4 by circular dichroism

Abstract: The conformation and stability of Escherichia coli derived recombinant human interleukin 4 (rhuIL-4) have been examined by circular dichroism (CD). Protein unfolding was detected by ellipticity changes at 222 nm with increasing concentrations of guanidine hydrochloride (GdnHCl). The unfolding midpoint ([GdnHCl]1/2) was 3.7 M, the free energy of unfolding, (delta GDH2O), was 5.9 kcal/mol and the dependence of delta GD on the GdnHCl concentration (m) was 1.6 (kcal/mol)/M. This unfolding was demonstrated to be re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…As shown here, IL‐4, IL‐5 and sCD30 all decreased, while IFN‐ γ was not as strongly affected by GSH/NAC treatment as determined by ELISA. Interestingly, it has previously been shown that the structural disulphides in IL‐4 and IL‐5 [39, 46] are necessary for their biological activity [47, 48]. Indeed, when we incubated rhIFN‐ γ with different concentrations of NAC, the levels of IFN‐ γ did not change.…”
Section: Discussionmentioning
confidence: 85%
“…As shown here, IL‐4, IL‐5 and sCD30 all decreased, while IFN‐ γ was not as strongly affected by GSH/NAC treatment as determined by ELISA. Interestingly, it has previously been shown that the structural disulphides in IL‐4 and IL‐5 [39, 46] are necessary for their biological activity [47, 48]. Indeed, when we incubated rhIFN‐ γ with different concentrations of NAC, the levels of IFN‐ γ did not change.…”
Section: Discussionmentioning
confidence: 85%
“…As yet no X-ray structure is available for IL-4, although preliminary studies have shown that the molecule forms well-ordered crystals that diffract to beyond 2.8-A resolution and so are suitable for detailed diffraction analysis (Cook et al, 1991). In addition, CD studies of the protein in solution have shown that it has a high percentage of a-helical structure and has a high stability over a wide range of solvent conditions (Windsor et al, 1991).NMR spectroscopy is a powerful technique that can now be used to give detailed descriptions of protein structures (Wiithrich, 1989). As NMR provides the structure of proteins in solution, the method complements the use of X-ray diffraction for the determination of protein structures.…”
mentioning
confidence: 99%
“…• • . Recently, biophysical and protein-chemical studies .on the, aromatic side chains of human IL4 have been reported [10,12]. We have singly• replaced the .two tyrosines by aspartic acid and the • tryptophane by • arginfne, yielding the muteins YS6D, 1240 and W91R.…”
mentioning
confidence: 99%
“…2). According to drcular dichroism rn:easurements the tryptophane is largely accessible to the solvent , [12]. It.…”
mentioning
confidence: 99%
See 1 more Smart Citation